2009
DOI: 10.1038/gt.2009.122
|View full text |Cite
|
Sign up to set email alerts
|

Partial protection against SIV challenge by vaccination of adenovirus and MVA vectors in rhesus monkeys

Abstract: This study explores the effect of priming rhesus monkeys with an Ad5/35 vector expressing simian immunodeficiency virus (SIV) gag and gp120, and then boosting the animals with an modified vaccinia virus Ankara (MVA) vector encoding the same antigens after a 2-month interval. The animals were intravenously challenged with 100 TCID50 of highly pathogenic SIVmac239 virus 2 months after the booster vaccination. The priming vaccination induced robust SIV-specific cell-mediated and humoral immune responses, and boos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Along the same line, various vaccine strategies have been proposed to help restimulate HIV-specific immunity allowing HIV-infected patients to reduce time on antiretroviral therapy (ART) [7,8]. Various therapeutic vaccine candidates including peptide-, protein-, and viral vector-based vaccines have shown modest efficacy in experimental animal models [9,10] and patients [11][12][13][14][15][16][17][18]. Some candidate vaccines, such as ALVAC or Ad5, have induced potent increase in HIV-specific immune responses [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Along the same line, various vaccine strategies have been proposed to help restimulate HIV-specific immunity allowing HIV-infected patients to reduce time on antiretroviral therapy (ART) [7,8]. Various therapeutic vaccine candidates including peptide-, protein-, and viral vector-based vaccines have shown modest efficacy in experimental animal models [9,10] and patients [11][12][13][14][15][16][17][18]. Some candidate vaccines, such as ALVAC or Ad5, have induced potent increase in HIV-specific immune responses [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the virus displayed the cell tropism of Ad35. Using the Ad5/35 vector, we found that high immunogenicity of the vaccine was observed in both mice and non-human primates [39], [40]. Coupled with the evidence that an Ad5/35 vector transduces human dendritic cells more efficiently as compared with an Ad5 vector [41], these findings suggest that the Ad5/35-HIV vector is a promising candidate for human trials.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies showed that an adenovirus vector (Ad) vaccine against HIV could induce a strong Ag-specific immune response in humans and animal models [12,25,26,31,32]. However the Ad vaccine failed to protect against HIV infection in STEP human clinical trials [12,32].…”
Section: Resultsmentioning
confidence: 99%